Day 1 Wed, September 05, 2018 2018
DOI: 10.2118/191780-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery in Eagle Ford: Opportunities Using Huff-n-Puff Technique in Unconventional Reservoirs

Abstract: Although hydraulic fracturing in liquid-rich unconventional reservoirs (LUR) has become a norm, the recovery factor continues to be low. Use of enhanced oil recovery (EOR) techniques in LUR has recently become more popular to improve the recovery. The objective of this study is to numerically investigate the advantages and disadvantages of the application of the CO2 huff-n-puff technique in LUR formations having complex fracture networks. The study explores the fluid flow mechanisms for oil reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Moreover, they found that due to the misleading of the diffusion mechanism in pilot tests, there are some differences between laboratory and field tests that should be considered in the results. Pankaj et al (2018) investigated fluid flow behaviour mechanisms in fractured reservoirs in the Eagle Ford oilfield. They proposed a 3D petrophysical and geomechanical model to consider the fluid flow through natural fractures and improve the oil recovery by carbon dioxide injection.…”
Section: Public Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that due to the misleading of the diffusion mechanism in pilot tests, there are some differences between laboratory and field tests that should be considered in the results. Pankaj et al (2018) investigated fluid flow behaviour mechanisms in fractured reservoirs in the Eagle Ford oilfield. They proposed a 3D petrophysical and geomechanical model to consider the fluid flow through natural fractures and improve the oil recovery by carbon dioxide injection.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…They proposed a 3D petrophysical and geomechanical model to consider the fluid flow through natural fractures and improve the oil recovery by carbon dioxide injection. They concluded that the CO 2 huff-n-puff technique would be an efficient method as the gas phase can mobilize more through the tight pores and spaces (Pankaj et al, 2018).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…But no water production data were reported. An important reason is that water-cut for depletion stage is often quite stable except for an initial spike, which is largely due to the flowback to fracturing fluids (Pankaj et al 2018). But sometimes, water cut would surge if induced fractures invaded other zones, such as the overlaying Lodgepole formation in Bakken play (Jin et al 2017) or Bone Spring Formation in Delaware Basin (Pettit and Muirhea 2016).…”
Section: Field Observationsmentioning
confidence: 99%
“…Liu et al [35] designed a case study to evaluate the potential of CO 2 -EOR in the Bakken formation where promising results were observed. Pankaj et al [36] devised an Eagle Ford case study to investigate the CO 2 -EOR potential where they refuted the need for infill wells and reported an extra 9% increase in the recovery factor. Kerr et al [37] developed an Eagle Ford case study to engineer single-and multi-well CO2-EOR techniques and reasonable agreement with the field results was reported.…”
Section: Introductionmentioning
confidence: 99%